Morphology and Properties of Nanostructured Materials Based on Poly(trimethylene terephthalate) Fiber and Organoclay - Tayebi, H.; Bigdeli, A. (Asian Journal of Chemistry, 2011)
Nanostructured materials based on organically modified montmorillonite (OMMT) and poly (trimethylene terephthalate) fiber were prepared via melt-mixing of poly(trimethylene terephthalate) and organically modified nano clay in a twin screw extruder followed by fiber spinning. Rigid inorganic filler has been longtime used as a reinforcement agent for polymer materials. Recently, more work is focused on the possibility that using nano filler like organoclay for improving properties of fibers via melt intercalation. In this article, we reported our efforts on the change of morphology and properties of poly(trimethylene terephthalate)/nanoclay nanocomposite fibers. The effects of filler content and post processes on the morphology, crystallization behaviour, thermal stability and mechanical properties were investigated by SEM, DSC, TGA and mechanical test. A correlation was established between the changes in the nanostructure and mechanical properties. Exfoliated clay morphology was realized using a wide angle X-ray diffraction technique when both requirements of selecting an organic modifier that was thermodynamically compatible with polymer matrix and applying sufficient degree of shear stress were fulfilled.